Which estimator to measure local governments' cost efficiency? The case of Spanish municipalities - Isabel Narbón-Perpi\~ná; Maria Teresa Balaguer-Coll; Marko Petrović; Emili Tortosa-Ausina (SERIEs - Journal of the Spanish Economic Association, 2020)
We analyse overall cost efficiency in Spanish local governments during the crisis period (2008-2015). To this end, we first consider some of the most popular nonparametric methods to evaluate local government efficiency, data envelopment analysis and free disposal hull, as well as recent proposals, namely the order-m partial frontier and the nonparametric estimator proposed by Kneip et al. (Econom Theory 24(6):1663-1697, 2008). Second, to compare the four methods and choose the most appropriate one for our particular context and dataset (local government cost efficiency in Spain), we carry out an experiment via Monte Carlo simulations and discuss the relative performance of the efficiency scores under various scenarios. Our results suggest that there is no one approach suitable for all efficiency analysis. We find that for our sample of 1846 Spanish local governments, the average cost efficiency would have been between 0.5417 and 0.7543 during the period 2008-2015, suggesting that Spanish local governments could have achieved the same level of local outputs with about 25% and 46% fewer resources.
Keywords: C14; C15; H70; R15; 330; Efficiency; Local government; Monte Carlo simulations; Nonparametric frontiers